Distribusi Spasial Klorofil-A di Perairan Teluk Benoa Bali - Wianta, I Putu Gede Bayu Ade; Watiniasih, Ni Luh; Puspitha, Ni Luh Putu Ria (Journal of Marine and Aquatic Sciences, 2021)
Benoa Bay is an estuary that gets input of waste and nutrients from six rivers and inderectly influenced water productivity in Benoa Bay. The nutrients flow from the river to domestic, industrial, and agricultural activities into Benoa Bay. The amount of nutrient inputs accumulated in Benoa Bay this could affect the chlorophyll-a consentrations. The purpose of this study was to determine the spatial distribution and influence nitrate and phosphate on chlorophyll-a concentration. Water surface sampling carried out on February 2019. The method used was purposive sampling and chlorophyll-a concentration was analysed using spectrophotometer Shimadzu UV-2600, based on the maximum absorption of four wavelengths (quadrichroic). The results showed that the chlorophyll-a concentration ranged from 0.22 - 8.53 g/m 3 with an average of 5.58 g/m 3 . Nitrate concentration ranged from 0,004 - 0,180 mg/L with an average 0,107 mg/L. Phosphate concentration ranged from 0,005 - 0,229 mg/L with an average 0,101 mg/L. Spatial distributions of chlorophyll-a concentration in Benoa Bay higher in the estuary area compare to sea area. The different concentration of chlorophyll-a in Benoa Bay were affected by physical and biological processes. The result of statistic regression of the nitrate and phosphate influence on chlorophyll-a concentration in Benoa Bay was 39,2% (R² = 0.392) for nitrate, meanwile 20,5% (R² = 0.205) for phosphate.